ISLAM AND TERRORISM: UNRAVELLING NARRATIVE BIASES IN AN INDONESIAN INDIE FILM - Nurmansyah, Mochamad Andhy; Ida, Rachmah; Irawanto, Budi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Since the 9/11 attack on the World Trade Center in New York in 2001, terrorism in the name of Islam has become a common occurrence in Indonesia. As a result, violent images of Islam widely circulated in the media. Islam and its minor images have permeated the Indonesian entertainment media landscape, including independent cinema. This study addresses the lack of research on Indonesian independent films with Islamic themes. In its earliest stage, this study studied how an independent movie, Train To Heaven (TTH), examined the language surrounding terrorism in the name of Islam. The analysis in this paper, which was conducted within the context of social semiotics, indicated that the sarcastic tones used in the text were consistent with the film's principal focus, which was rejecting violent acts in the name of Islam. TTH, an independent film that tackles the issue of terrorism committed in the name of Islam, frequently expresses resistance to the act at the outset of its cinematic portrayal. As the scenes develop, the story becomes increasingly ambiguous. TTH's antagonistic stance on alleged Islamic terrorism has not been maintained. The emergence of contradictions after the story, the TTH indie film's position, which has not been fully designed to address a specific alternative "voice," and the Islamic dynamics in Indonesia, which are not well mapped in discourse formation, are some of the particular factors that contributed to the ideological ambiguity of TTH's existence. Lastly, TTH's oppositional positioning or subtleties of resistance are questionable. The linguistic creation appears to be overtaken by ideological ambiguities. There is no doubt that Islamic doctrinal viewpoints will never include the death of God. The ending of the film was incongruous with the subject of criticism from the start, resulting in a confusing discourse about Islam and terrorism. Finally, this study reveals that TTH is ambiguous in defining the extent of its critique, whether it is directed at acts of terrorism in the name of Islam or Islamic beliefs. This study is limited by its focus on a single independent film, TTH, and is constrained by the evolving nature of Indonesian cinema and global perceptions of Islam and terrorism. Future research should examine a broader range of Indonesian indie films, explore the relationship between media representation, religion, and societal values, and consider audience reception studies to deepen the understanding of how such films are interpreted across different cultural and demographic contexts.